Virtual Reality-based Platformer Games Development for Elevating Architectural Heritage Awareness - Ahmad Nasikun; Bagas Y. Wijonarko; Raja Bagus Arief Rahman; Anugerah Galang Persada; Sunu Wibirama (IJITEE (International Journal of Information Technology and Electrical Engineering), 2018)
As a country with abundant traditional culture, Indonesia is facing serious challenge in conserving them. There is a need to promote the traditional culture to a wider area of people, particularly to the younger generation. Virtual world offers a new way of promoting a nation’s culture via Virtual Reality (VR). This research aims to develop a VR-based platformer mobile game to promote cultural awareness in a new and creative way for younger generation. In the game, a player can observe one famous architectural heritage in Yogyakarta—Mesjid Gedhe Kauman—in fun way of game. A survey is conducted to measure its success in reaching the predetermined goals and to measure its user experience (UX). The survey confirm that the VR-based platformer game helps them in learning cultural value of the architecture (62.5/100) and it is relatively easy to navigate (72.5/100). Moreover, it has a good user experience (UX) score—all are above 0.8, meaning that its users are generally comfortable in playing the game.